KEPEMILIKAN TANAH YANG DIPEROLEH MELALUI JUAL BELI DIBAWAH TANGAN SECARA MELAWAN HUKUM - Fairuuzah Fairuuzah; Listyowati Sumanto (Reformasi Hukum Trisakti, 2021)
The sale and purchase of land must be carried out before the Land Deed Making Officer in order to obtain Sale and Purchase Deed as a condition for registering the transfer of rights over the land. However, in practice, buying and selling is done underhand. A Case of unlawful land ownership occurred in Kuta Village, Central Lombok District. The problem: whether the sale and purchase carried out by Samah/seller to Ike Ratna Wulan and Nanang Abdul Mukti/third party can be categorized as unlawful act and how the dispute resolved in Supreme Court Decision Number 1979 K/PDT/2019. The research is normative and descriptive legal research, using primary and secondary, The data is analyzed qualitatively and conclusions are drawn using deductive logic method.. The conclusion: the sale and purchase carried out in 2006 between Samah/Seller and Sahdan was valid because it met the material and formal requirements. The sale and purchase in 2013 between Samah/seller to Ike Ratna Wulan and Nanang Abdul Mukti/Third Party was categorized as an unlawful act because it fulfilled the elements in article 1365 of Civil Code so that the sale and purchase was illegal and null and void because Samah has no right to sell the land.